Feeding behaviour of epi-anecic earthworm species and their impacts on soil microbial communities. (October 2018) - Hoeffner, Kevin; Monard, Cécile; Santonja, Mathieu; Cluzeau, Daniel
Abstract: Earthworms contribute to numerous ecosystem services provided by soils. Most of the studies focusing on the contributions of earthworms on leaf litter decomposition were conducted by comparing distinct ecological categories (epigeic, epi-anecic, anecic strict and endogeic), whereas their specific contributions within a given ecological category remains largely unknown. In this context, the aim of this study was to determine the contribution of four epi-anecic earthworm species ( Lumbricus rubellus, Lumbricus festivus, Lumbricus centralis and Lumbricus terrestris) to the leaf litter decomposition of three plant species ( Lolium perenne, Holcus lanatus and Corylus avellana ) with contrasted litter traits located at both the soil surface and at a depth of 10 cm. Fungal and bacterial communities inhabiting epi-anecic earthworm burrows were also assessed using T-RFLP analysis. Epi-anecic earthworms improved the leaf litter mass loss solely at the soil surface, while leaf litter mass loss was mainly due to microbial activity at 10 cm deep. Leaf litter mass loss was positively correlated to the initial biomass of the epi-anecic earthworms and the intensity of this relationship was dependent on litter type. Interestingly, L. festivus seemed to have a higher contribution to surface leaf litter mass loss that was linked to a stimulation of the fungal communities in its burrows. Fungal communities were thus impacted by both the litter type and the epi-anecic earthworm identity whereas soil bacterial diversity and richness were stimulated in the earthworm burrows whatever the epi-anecic earthworm species considered. Overall, epi-anecic earthworms contributed to enhance the diversity of the drilospheric microbiota. Highlights: Epi-anecic earthworms feed preferentially on surface litter. Epi-anecic earthworms exhibit the same sensitivity to litter quality. Litter mass loss is highly correlated to epi-anecic earthworms' biomass. Bacterial richness and diversity is enhanced by the presence of epi-anecic earthworms. Fungal community structure is modified in presence of epi-anecic earthworms.